Fururndu, a Meat Substitute from Fermented Roselle (Hibiscus sabdariffa L.) Seed: Investigation on Amino Acids Composition, Protein Fractions, Minerals Content and HCl-Extractability and Microbial Growth - A. Yagoub, Abu El Gasim; Mohammed, Mohammed A. (Pakistan Journal of Nutrition, 2008)
Indigenous furundu is prepared by cooking the karkade (Hibiscus sabdariffa L.) seed and then fermenting it for 9 days. Physicochemical properties and HCl-extractability of minerals of the karkade seeds and of furundu ferments were analyzed. Microbial growth during fermentation was also screened. Furundu fermentation resulted in increase in total protein of the karkade seed, suggesting changes in dry matter composition. Significant decrease in karkade seed protein fractions, albumin plus globulin and prolamin and a significant increase in G1, G2 and G3 on fermentation was found. Also a decrease in total acidity and pH was observed. The amino acids profile of the karkade seed was dominated by glutamic acid, aspartic acid and arginine. The sulfur amino acids (Methionine and cystine) and threonine were the limiting amino acids in karkade seed and they remained limiting in furundu. Slight mobilization in amounts of some amino acids, simultaneously with increase in the level of ammonia during preparation of furundu was noticed. The contents of K, Na, Cu, Mn and Fe of the karkade seed were decreased significantly in furundu. The HCl-extractability of K, Mn and Fe in karkade seed was improved in furundu product. Fermentation of the cooked seed increased growth of bacteria, yeasts and moulds. The endospore-forming Bacillus species is predominately the active organism in the substrate medium.